2005
DOI: 10.1002/ar.a.20197
|View full text |Cite
|
Sign up to set email alerts
|

Role of thyroid hormone in the initiation of EGF (epidermal growth factor) expression in the sublingual gland of the postnatal mouse

Abstract: The effect of triiodo-L-thyronine (T 3 ) and propylthiouracil (PTU) on the initiation of epidermal growth factor (EGF) expression in the sublingual glands (SLGs) of postnatal mice was investigated by indirect enzyme-labeled and immunogold antibody methods for light and electron microscopy, respectively. In normal males, EGF immunoreactivity first appeared in a few scattered granular cells of striated ducts (SDs) at 5 weeks of age, and the immunoreactive cells had increased in number at 6 weeks of age. No EGF e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…[2][3][4] In the SLGs of intact mice, a few scattered GCT-like granular cells are known to occur frequently in the striated ducts of adult males, but not females. 1,6,11 Even after long exposure to high levels of DHT and/or T 3 , in the same way as in this study, a few GCT-like granular cells were always induced in the SLGs of females. 1,6 However, the present study showed that such granular cells were rarely induced in the parotid glands of hormoneinjected female mice.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…[2][3][4] In the SLGs of intact mice, a few scattered GCT-like granular cells are known to occur frequently in the striated ducts of adult males, but not females. 1,6,11 Even after long exposure to high levels of DHT and/or T 3 , in the same way as in this study, a few GCT-like granular cells were always induced in the SLGs of females. 1,6 However, the present study showed that such granular cells were rarely induced in the parotid glands of hormoneinjected female mice.…”
Section: Discussionsupporting
confidence: 50%
“…1,7,11,17 Using normal female 1 and hypophysectomized male 7 mice SLGs, our previous study established that combinations of thyroid hormones and androgens converted a few GST cells to GCT-like fully fledged granular cells. The same conversion occurred in a few GST cells in the parotid gland in response to external hormones.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations